Cultura popular e Turismo: O Ceará nos anos 1970 / Popular Culture and Tourism: Ceará, Brazil, in the 70’s - de Oliveira, Ana Amélia Rodrigues (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> O artigo analisa o processo de atribuição de valor econômico à cultura popular, a partir da sua vinculação à atividade turística. Até a década de 1950, a cultura popular era entendida socialmente, apenas como um elemento constitutivo da identidade brasileira, calcada nos ideais de pureza e autenticidade. Com a criação de órgãos como o Banco do Nordeste e a Sudene, o governo federal tenta inserir o Nordeste na lógica de desenvolvimento capitalista, e começa a ver na produção popular uma possibilidade de gerar renda a partir do investimento na produção artesanal. O desenvolvimento do turismo influenciará na inserção das tradições populares no circuito econômico como atrativo turístico. Popular Culture and Tourism: Ceará, Brazil, in the 70’s - This paper analyzes the process of assigning economic value to popular culture and its link to tourism. Until the 1950's, popular culture was understood socially in an ideal of purity and authenticity, as a constitutive element of national identity. With creation of institutions such as Banco do Nordeste and Sudene, federal government intends to include the Brazilian Northeast in the capitalist development logic, and see the popular production as a possibility to generate income from investment in craft production. Tourism development will mark the insertion of popular traditions in the economic circuit as a tourist attraction. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->